The Argentine workers’ anti-war movement during the Korean War (1950-1951) - Kabat, Marina (2024)
During the Korean War, the United States, invoking previous treaties, asked Argentina and all Latin American governments for support. Notably, the US requested them to send troops to participate in the military conflict. The Argentine president, Juan Domingo Perón, looking forward to economic aid from the US, promptly agreed and began the preparations. But his arrangements were thwarted by a pacifist campaign organised by the Argentine Communist Party. Women, youth, and unionised workers were essential to this campaign. Particularly decisive was a mass demonstration of railroad workers in Rosario city. The campaign, despite harsh repression from the government, achieved its objectives, and no Argentine soldier was sent to fight in the Korean War, a testament to the success of the resistance.